Phytoplacton Community In The Asahan River As A Fish Cultivation - Ika Rosenta Purba (International Journal of Science and Environment (IJSE), 2025)
This study aims to analyze the structure of the phytoplankton community in the Asahan River. Using a descriptive survey. Determination of the location of phytoplankton sampling was carried out by purposive sampling. The results showed that overall phytoplankton were found in three divisions Crysophyta, Cyanophyta and Chlorophyta and 17 genera. The highest relative abundance (KR) was found in the genus Pediastrum of 12.7 with a diversity index of an average of 2.39, an evenness index of 0.35 and a dominance index of 0.16. The results of the physical factor measurements are an average turbidity of 3.53 NTU, an average water temperature of 32oC and an average water pH of 6. The results of the average water chemical factor measurements are water DO of 5.15 ppm, BOD = 1.85 ppm, COD = 26.45 ppm, CO2 levels = 18.29 ppm and mercury (Hg) levels measured range from 0 - 0.05 ppm. In conclusion, the abundance of phytoplankton is in the low category with a moderate diversity index and the waters are classified as stable.